Integration of RPS and Sub-CPMK Grading in INSPIRE for OBE Evaluation - Tangui, Monica Gabriela; Sambul, Alwin; Paturusi, Sary (Universitas Sam Ratulangi, 2026)
Abstract — The Semester Learning Plan (RPS) acts as a learning contract that aligns outcomes, learning activities, and assessment. In many study programs, RPS authoring and grading are still handled as separate processes, making the link between Sub-CPMK, assessments, and student grades difficult to trace and prone to weighting errors. This paper presents the design of an integrated RPS and grading workflow in the INSPIRE application to support Outcome-Based Education (OBE) at Universitas Sam Ratulangi. The integration enables course RPS owners to define Sub-CPMK, select assessment types, and distribute weights under consistent validation rules, while lecturers can submit grades via automatic synchronization from course assignments or manual entry for specific Sub-CPMK. The application also provides an automatic evaluation-plan preview that calculates weight distributions, a grade recap, and a grade-lock mechanism to preserve data integrity once finalized. The resulting design improves efficiency and transparency of grading and strengthens alignment with OBE principles, including institutional policies that prioritize participatory activities and project outcomes. The integrated workflow produces more accountable assessment records and better-prepared academic data for reporting and continuous improvement. Keywords — semester learning plan; Sub-CPMK; assessment; grading; OBE.